Liquid nitrogen historical and current usage of the central helium liquefier at SNS. Issue 1 (November 2015) - DeGraff, B; Howell, M; Kim, S; Neustadt, T
Abstract: The main cryogenic system for the Spallation Neutron Source (SNS) is comprised of a 4-K cold box, a 2-K cold box, six warm compressors, and ancillary support equipment. This system has been cold and operating with little disruption since 2005. Design and operation of liquid nitrogen (LN2) supplied from a single 20, 000-gallon supply Dewar will be discussed. LN2 used to precool the 4-K cold box heat exchanger started to increase around 2011. LN2 Consumption during 2012 and 2013 was almost double the nominal usage rate. Studies of this data, plant parameter changes to respond to this information, and current interpretations are detailed in this paper. The usage rate of LN2 returned to normal in late 2013 and remained there until recent additional changes. Future study plans to understand potential causes of this including contamination migration within the 4-K cold box will also be addressed.